Managed DirectX 9 : graphics and game programming : kick start. - Miller, Tom, ....- (Indianapolis : Sams, 2004)
Managed DirectX was released with the latest version of the core DirectX libraries in DirectX9. It enables developers using the new .NET languages (i.e. C#, VB.NET, etc.) to develop rich multimedia applications with DirectX. Unfortunately the Managed DirectX runtime was released without adequate documentation, and developers are having a hard time figuring out the best way to write managed applications. This book covers how to use the Managed DirectX objects, how they differ from the core DirectX libraries, and how to create these rich multimedia applications in C#. It also covers in depth graphics techniques and the new high-level shader language shipping with DirectX9
Keywords: Driedimensionele beeldverwerking; Programmeren